The Effects of Setting Budget Goals and Task Uncertainty on Performance: A Theoretical Analysis - Hirst, Mark K. (The Accounting Review, 1987)
[This paper discusses the effects of setting budget goals on task performance in different task situations. The main hypothesis developed from this analysis is that the effect of setting specific, difficult budget goals on task performance depends on the level of task uncertainty. Specifically, it is argued that, where task uncertainty is high, setting budget goals is less effective in promoting task performance than where task uncertainty is low. In addition, it is suggested that, although limited, available evidence is consistent with this hypothesis. Finally, the research implications of the analysis are considered.]